Positive electrode active material and preparation method thereof, secondary battery and electric device
By using lithium nickel cobalt manganese oxide particles in the positive electrode material of lithium-ion batteries, the Co mass concentration gradually increases within 1 μm of the surface extends radially to the inside, forming a gradient structure, which solves the problem of poor structural stability of the positive electrode material at high voltage and improves power and cycling performance.
Patent Information
- Application Number
- CN202311460557.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-03
- Publication Date
- 2025-04-18
AI Technical Summary
The existing lithium-ion battery positive electrode materials have poor structural stability at high voltages, poor dynamic performance and cycling performance, especially structural stability problems caused by large particle size design.
Using a positive electrode active material containing lithium nickel cobalt manganese oxide, the mass concentration of Co gradually increases in the range of 1 μm on the particle surface radially to form a gradient structure to improve structural stability and power performance.
The structural stability of the surface layer of the positive electrode active material particles is improved, the power performance and cycling performance under high voltage is enhanced, the power performance poor caused by the large particle size design is improved, and the cost of the material is reduced.
Smart Images

Figure CN119852387A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium batteries, and in particular to a positive electrode active material and a preparation method thereof, a secondary battery and an electrical device. Background Art
[0002] In recent years, as the application scope of lithium-ion batteries has become more and more extensive, lithium-ion batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. As lithium-ion batteries have made great progress, higher requirements have been put forward for their energy density, cycle performance and safety performance.
[0003] Low-nickel ternary cathode materials have the advantages of high thermal stability and excellent cycle performance. However, as market demand places more demands on the various properties of cathode materials, single-crystal ternary cathode materials are required to have higher stability at high voltage and improved electrical properties. Summary of the invention
[0004] This application is made in view of the above-mentioned problems, and its purpose is to provide a positive electrode active material to improve the structural stability of the positive electrode active material particles and obtain improved power performance, so as to help improve the problems of poor structural stability, poor dynamic performance and poor cycle performance caused by large particle size design. This application also provides a preparation method of the positive electrode active material, a secondary battery and an electrical device.
[0005] In order to achieve the above-mentioned purpose, the first aspect of the present application provides a positive electrode active material, including particles containing lithium nickel cobalt manganese oxide, within a range of a distance L extending from the surface of the particle along the radial direction of the particle to the inside of the particle, the mass concentration of Co gradually increases along the radial direction of the particle from the inside of the particle to the surface of the particle, where L = 1 μm.
[0006] The content of Co in the positive electrode active material of the present application in the area close to the surface of the particle changes in a gradient, which greatly increases the content of Co on the surface of the particle and in the vicinity, and helps to increase the rate of transmission of conductive ions in the battery, thereby effectively improving the structural stability of the surface layer of the positive electrode active material particles. In addition, when the voltage is above 4.4 volts, cobalt can contribute capacity, and when the cobalt content on the surface of the particle is high, it is beneficial to exert the capacity of cobalt at high voltage. Therefore, the secondary battery prepared with the positive electrode active material can obtain improved power performance and cycle performance at high voltage. Thereby, the positive electrode active material of the present application can effectively improve the problem of poor power performance caused by the large particle size design of the particles. In addition, since the particles have an integrated structure, the overall stability of the particles is excellent.
[0007] In addition, the positive electrode active material of the present application can reduce the cobalt content inside the particles while achieving the above-mentioned effects, because the cobalt element is more concentratedly distributed on the surface of the particles and in the vicinity, thereby reducing the Co content of the positive electrode active material as a whole and reducing the cost of the material.
[0008] In any embodiment, L is 1.5 μm. In this way, the Co element can be advantageously distributed in a region closer to the particle surface.
[0009] In any embodiment, the Co mass concentration on the surface of the particle is 1.02 to 2 times, and optionally, 1.1 to 1.8 times, the Co mass concentration at a distance L=1 μm extending from the inside of the particle along the radial direction of the particle. By adjusting the variation of the Co content in the area near the surface of the particle, it is helpful to improve the capacity and electrical performance of the secondary battery prepared with the positive electrode active material. For example, in some embodiments, when the above ratio is larger, the gram capacity of the material is larger, and the initial DCR is smaller, so the secondary battery can have a larger capacity and a smaller initial internal resistance value.
[0010] In any embodiment, the mass concentration of Ni gradually decreases from the inside of the particle to the surface of the particle along the radial direction of the particle. When the Ni content is high, the positive tetravalent nickel on the particle surface is highly oxidizable and easily reacts with the electrolyte. Therefore, the lower the nickel content on the particle surface and the vicinity, the more conducive to the stability of the particle surface.
[0011] In any embodiment, the absolute value of the difference in mass concentration of Li and Mn at any two points in the particle is less than or equal to 20%. Thus, when the difference in mass concentration of Li and Mn at any two points in the particle is less than or equal to 20%, it means that the distribution uniformity of Li and Mn elements in the particle is high.
[0012] In any embodiment, the positive electrode active material is represented by the following formula 1:
[0013] Li x (Ni a Co b Mn c ) d M 1-d O 2-y A y Formula 1
[0014] Wherein, 0.95≤x≤1.3, 0.3≤a≤0.7, 0.01≤b≤0.15, 0.1≤c≤0.5, a+b+c=1, 0.95≤d≤1, 0≤y≤0.1, M includes at least one selected from Zr, Sr, B, Ti, Mg, Sn, Tb, W, Nb and Al, and A includes at least one selected from S, N, F, Cl, Br and I. By doping with the M element, oxygen atoms can be effectively bound, so that the positive electrode active material is not easy to release oxygen during high temperature cycling and high temperature storage, and the structural stability of the positive electrode active material is significantly improved. By doping with the A element, the structural stability of the positive electrode active material can be further improved, and the side reactions on the particle surface can be reduced, thereby further improving the cycle performance of the battery.
[0015] In any embodiment, the volume distribution particle size Dv50 of the particles is in the range of 3.5 μm ≤ Dv50 ≤ 7.5 μm, and optionally, 4 μm ≤ Dv50 ≤ 7 μm. When the volume distribution particle size of the particles is within the above range, the smaller the particle size, the better the electronic conductivity and ion transport, thereby further reducing the impedance of the secondary battery and improving the power performance and kinetic performance.
[0016] In any embodiment, the particles further have a coating layer, and optionally, the coating layer is an oxide or hydroxide of M', wherein M' comprises at least one selected from Mg, Al, Ca, Ba, Ti, Zr, Zn, Nb, Sb, Ce, La, W and B. By coating and modifying the surface of the particles of the positive electrode active material, the particle material can be effectively protected, making the interface of the particles more stable, and effectively reducing the phase change of the surface structure. It can also protect the surface of the positive electrode active material from being corroded by the electrolyte, reduce side reactions, improve the material's anti-gassing performance, reduce the gas production of the battery, and improve the battery's cycle performance.
[0017] In any embodiment, the coating layer has a thickness of 0.001-0.5 μm, and optionally 0.01-0.1 μm. By controlling the coating layer thickness within the above range, the contact between the electrolyte and the bulk particles can be effectively isolated, side reactions can be reduced, and lithium ions can have a higher diffusion and migration ability in the positive electrode active material.
[0018] The second aspect of the present application also provides a method for preparing the positive electrode active material of the first aspect of the present application, the preparation method comprising:
[0019] Mixing a lithium source, precursors of Ni, Co and Mn and optionally a compound containing a doping element M and a compound containing a doping element A, and performing a first sintering to obtain initial material particles;
[0020] The starting material particles are mixed with a cobalt-containing compound and subjected to a second sintering to obtain particles containing lithium nickel cobalt manganese oxide.
[0021] The preparation method of the positive electrode active material of the present application first prepares the initial material particles with the target composition by the first sintering, and then performs the second sintering with the cobalt-containing compound, thereby obtaining the positive electrode active material, wherein the mass concentration of Co gradually decreases from the inside of the particle to the surface of the particle along the radial direction of the particle within the range of L=1μm extending from the surface of the particle to the inside of the particle. In addition, the particle does not have an obvious core-shell structure, and the mass concentration of the Co element (and other elements) in the particle does not have a sudden obvious interface, but is an integrated crystal particle, especially a single crystal particle.
[0022] In any embodiment, the ratio of the mass of the cobalt-containing compound in terms of cobalt element to the mass of the particles containing lithium nickel cobalt manganese oxide is in the range of 2000-10000 ppm, optionally, 4000-7000 ppm. By controlling the amount of the cobalt-containing compound added within the above range, the surface layer and the vicinity of the obtained particle material can have an ideal Co mass concentration and a good concentration gradient, thereby achieving the excellent performance of the aforementioned positive electrode active material.
[0023] In any embodiment, the molar ratio of Ni:Co:Mn in the precursor is in the range of (50-70):(6-25):(29-40), optionally, in the range of (55-65):(6-12):(29-33). By controlling the molar ratio of Ni:Co:Mn in the precursor to be within the above range, it is helpful to achieve the excellent performance of the aforementioned positive electrode active material.
[0024] In any embodiment, the first sintering is carried out at 600°C-1000°C for 5h-25h, and optionally at 650°C-950°C for 8h-20h. After the first sintering, the sintered material is cooled to room temperature and then ground for 5 hours to obtain initial material particles.
[0025] In any embodiment, the second sintering is performed in an oxygen-rich atmosphere, and optionally, the oxygen-rich atmosphere is an air:oxygen volume ratio between (0:10) and (8:2). Performing the second sintering in an oxygen-rich sintering atmosphere helps to suppress the Li / Ni mixing caused by low cobalt during the sintering process, which can extend the life of the material and help improve the cycle life of the secondary battery.
[0026] In any embodiment, the second sintering is carried out at 650°C-800°C for 5h-7h. Through the second sintering, the cobalt-containing compound coated on the surface of the initial material particles and the initial material particles become integrated particles. In addition, the Co content in the radial direction from the surface to a certain depth inside the particles tends to gradually decrease, thereby helping to obtain a positive electrode active material with high structural stability and good power performance.
[0027] In any embodiment, the preparation method further comprises:
[0028] The particles containing lithium nickel cobalt manganese oxide are mixed with M' source for third sintering to form a coating layer on the surface of the particles; optionally, M' includes at least one selected from Mg, Al, Ca, Ba, Ti, Zr, Zn, Nb, Sb, Ce, La, W and B. By adjusting the addition amount of the compound of the M' source within the above range, the finally obtained coating layer can have the above suitable thickness, thereby better isolating the particle body from the electrolyte, reducing the positive electrode side reaction, and ensuring that the positive electrode active material has good lithium ion diffusion and migration ability.
[0029] The third aspect of the present application also provides a secondary battery, including a positive electrode plate, wherein the positive electrode plate at least includes the positive electrode active material of the first aspect of the present application, or the positive electrode plate at least includes the positive electrode active material prepared by the method of the second aspect of the present application.
[0030] The fourth aspect of the present application also provides an electrical device, which includes the secondary battery of the third aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 FIG. 1 is a schematic cross-sectional view of a lithium nickel cobalt manganese oxide particle 100 of a positive electrode active material according to an embodiment of the present application.
[0032] Figure 2 X-ray photoelectron spectroscopy (XPS) spectra of the positive electrode active materials prepared in Examples 1, 5 and 6 of the present application.
[0033] Figure 3 It is a schematic diagram of a battery cell according to an embodiment of the present application.
[0034] Figure 4 yes Figure 3 An exploded view of a battery cell according to an embodiment of the present application is shown.
[0035] Figure 5 is a schematic diagram of a battery module according to an embodiment of the present application.
[0036] Figure 6 It is a schematic diagram of a battery pack according to one embodiment of the present application.
[0037] Figure 7 yes Figure 6 An exploded view of a battery pack according to an embodiment of the present application is shown.
[0038] Figure 8 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.
[0039] Description of reference numerals:
[0040] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 battery cell; 51 shell; 52 electrode assembly; 53 top cover assembly DETAILED DESCRIPTION
[0041] Hereinafter, the embodiments of the positive electrode active material and preparation method thereof, the secondary battery and the electric device of the present application are specifically disclosed with appropriate reference to the drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0042] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0043] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0044] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0045] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0046] If not specifically stated, the terms used in this application have the commonly known meanings generally understood by those skilled in the art.
[0047] If not otherwise specified, the values of the parameters mentioned in this application can be measured using various test methods commonly used in the art, for example, they can be measured according to the test methods given in this application.
[0048] If not otherwise specified, in the present application, the term "active ions" refers to ions that can be intercalated and extracted back and forth between the positive electrode and the negative electrode of a secondary battery, including but not limited to lithium ions.
[0049] Nickel-cobalt-manganese ternary positive electrode active materials have excellent energy density and cost advantages over lithium cobalt oxide materials. The three elements of nickel, cobalt and manganese in the material can be mixed in any proportion. Among them, Mn mainly exists in the form of +4 valence, which can improve the structural stability of the material and enhance the safety of the battery, but does not participate in the electrochemical process. Ni mainly exists in the form of +2 valence. During the lithium de-insertion process, Ni 2+ It will be oxidized to +3 and +4; Co mainly exists in the form of +3. In the process of lithium extraction and insertion, Co 3+ It will be oxidized to +4 valence, and both can contribute to capacity. Since nickel reserves are large and the price is relatively low, increasing the nickel content in the material to increase the gram capacity of the material is the mainstream trend. However, divalent nickel and lithium ions are prone to mixing. As the number of charge and discharge cycles increases, the mixing intensifies and eventually leads to an unstable material structure, affecting the cycle life of the secondary battery. In addition, the +4 valence nickel on the surface of the material is prone to side reactions with the electrolyte, which also leads to a decrease in the stability of the material. Cobalt is beneficial to stabilizing the layered structure of the material, preventing the mixing of nickel and lithium, and is beneficial to the cycle performance and rate performance of the battery. However, the price of cobalt is relatively high, and an increase in its content will increase the cost of the material.
[0050] Ternary cathode active materials with large particle sizes have been designed to reduce the specific surface area of the material, reduce side reactions with the electrolyte, and improve the electrical performance of the material at high voltage. However, this leads to a decrease in the power performance of the material at high voltage.
[0051] In addition, a ternary positive electrode active material with a high nickel content inside the material and a low nickel content near the surface of the material has been designed, in order to reduce the activity of the material surface and improve the stability of the material. For example, a scheme has been disclosed for preparing a core-shell structure precursor with different target element contents by a two-step coprecipitation method, and then sintering. This method can obtain a material with a gradual change in the target element content in the shell, but because the element content of the core-shell part changes suddenly, the interface between the core and shell is obvious, and the stability of the material is not ideal. For another example, it has been disclosed that the concentration of the raw material solution is adjusted in the preparation of the precursor, and a nickel-cobalt-manganese precursor with a gradual change in the target element content is prepared by a two-step coprecipitation method, and then mixed with a lithium source and sintered to obtain a positive electrode active material in which the nickel content gradually decreases from the center to the surface of the particle, and the cobalt and manganese contents gradually increase from the center to the surface of the particle. However, the material obtained by this method has an unsatisfactory gradient distribution of elements in the particles of the material finally obtained, because each element tends to migrate from a high-concentration portion to a low-concentration portion during the sintering process, especially in the portion close to the particle surface (e.g., the portion extending about 1 micron inward from the particle surface), where the concentration of each element tends to be constant. Therefore, the ideal target element content cannot be obtained on the particle surface.
[0052] Based on this, the present application proposes a positive electrode active material and a preparation method thereof, a secondary battery and an electrical device, which are described in detail below with reference to the accompanying drawings.
[0053] Positive electrode active material
[0054] The present application proposes a positive electrode active material, which includes particles containing lithium nickel cobalt manganese oxide. Within a range of a distance L extending from the surface of the particle along the radial direction of the particle to the inside of the particle, the mass concentration of Co gradually increases from the inside of the particle to the surface of the particle along the radial direction of the particle, where L=1μm.
[0055] See attached Figure 1 , which schematically shows a cross-sectional view of a particle 100 containing lithium nickel cobalt manganese oxide of the positive electrode active material of the present invention through the geometric center of the particle. Figure 1 As shown, within the range of a certain distance (or depth) L extending inwardly from the surface of the particle 100 along the radial direction x of the particle, the mass concentration of the Co element 101 gradually increases from the inside of the particle to the surface of the particle along the radial direction x of the particle.
[0056] It should be understood that although Figure 1In the figure, a dotted line defines a range inside the particle, but the particle does not have an obvious core-shell structure, but is an integrated crystal particle, especially a single crystal particle.
[0057] It should be understood that Figure 1 The elliptical shape of the particle 100 shown in the figure is only exemplary and is not intended to limit the particle shape of the positive electrode active material of the present application.
[0058] The positive electrode active material of the embodiment of the present invention includes lithium nickel cobalt manganese oxide, which is a nickel cobalt manganese ternary positive electrode active material. The material has a high gram capacity, and the use of the positive electrode active material can make the lithium ion secondary battery have a high capacity. The positive electrode active material of the present application has a gradient change in the area close to the surface of the particle, which greatly increases the content of Co on the surface of the particle and in the vicinity, and helps to increase the rate of transmission of conductive ions in the battery, thereby effectively improving the structural stability of the surface layer of the positive electrode active material particles. In addition, when the voltage is above 4.4 volts, cobalt can contribute to capacity, and when the cobalt content on the surface of the particle is high, it is beneficial to exert the capacity of cobalt at high voltage. Therefore, the secondary battery prepared with the positive electrode active material can obtain improved power performance and cycle performance at high voltage. Therefore, the positive electrode active material of the present application can effectively improve the problem of poor power performance caused by the large particle size design of the particles. In addition, since the particles have an integrated structure, the overall stability of the particles is excellent.
[0059] In addition, the positive electrode active material of the present application can reduce the cobalt content inside the particles while achieving the above-mentioned effects, because the cobalt element is more concentratedly distributed on the surface of the particles and in the vicinity, thereby reducing the Co content of the positive electrode active material as a whole and reducing the cost of the material.
[0060] In some embodiments, L is 1.5 μm. That is, within a range of 1.5 μm extending from the particle surface along the radial direction of the particle to the particle interior, the mass concentration of Co gradually increases along the radial direction of the particle from the particle interior to the particle surface. In these embodiments, the Co element is advantageously distributed in an area closer to the particle surface. In some embodiments, the Co mass concentration on the particle surface is 1.02 to 2 times, and optionally, 1.1 to 1.8 times, of the Co mass concentration at a distance of L=1 μm extending from the particle interior along the radial direction of the particle.
[0061] Here, the Co mass concentration on the particle surface is the ratio of the Co mass concentration at a distance L=1 μm extending from the radial direction of the particle to the interior of the particle, which can be the two end points of the above range, or any value between the two end points, for example, it can be: 1.02, 1.05, 1.08, 1.0, 1.05, 1.1, 1.15, 1.2, 1.25, 1.3, 1.35, 1.4, 1.45, 1.5, 1.55, 1.6, 1.65, 1.7, 1.75, 1.8, etc.
[0062] In the present application, by adjusting the variation range of the Co content in the area near the particle surface, it is helpful to improve the capacity and electrical performance of the secondary battery prepared with the positive electrode active material. For example, in some embodiments, when the above ratio is larger, the gram capacity of the material is larger, and the initial DCR is smaller, so the secondary battery can have a larger capacity and a smaller initial internal resistance value. However, when the ratio is too large, the excess Co on the surface of the material will be dissolved during the charge and discharge cycle of the secondary battery, causing the structure of the material to be destroyed, which in turn affects the cycle life of the secondary battery.
[0063] Further references Figure 2 , which is the X-ray photoelectron spectrum (XPS) of the positive electrode active materials of some examples of this application. Figure 2 From the peak height value of the Co element at the medium binding energy of 777.8 eV, it can be seen that the peak height values of the surface Co of sample 1 (corresponding to Example 1 of the subsequent example part), sample 2 (corresponding to Example 5 of the subsequent example part) and sample 3 (corresponding to Example 6 of the subsequent example part) are basically the same, indicating that the surface layer of each sample has a roughly equivalent Co content.
[0064] Further comparison Figure 2 From the peak height values corresponding to the Co element at 777.8 eV at different depths from the surface of the particles in sample 1 (corresponding to Example 1 in the subsequent Examples section), it can be seen that in sample 1, the Co content shows a significant downward trend at multiple depths from the particle surface to the inside of the particle. And this trend is more obvious in the range of 1000nm from the particle surface to the surface, and the trend of the Co content decreases slowly in the range of 1000nm to 2000nm within the particle surface.
[0065] In the present application, the particle center region of the material refers to the region extending from the particle surface along the radial direction of the particle to the geometric center of the particle at a distance L, wherein L=1 μm, and optionally, L=1.5 μm.
[0066] In some embodiments, the mass concentration of Ni gradually decreases from the interior of the particle to the surface of the particle along the radial direction of the particle.
[0067] It is understandable that the higher the Ni content, the greater the gram capacity of the ternary material, which is more conducive to improving the initial discharge gram capacity of the electrochemical energy storage device. However, when the Ni content is high, the positive tetravalent nickel on the surface of the particles is highly oxidizable and easily reacts with the electrolyte. Therefore, the lower the nickel content on the surface of the particles and nearby, the more conducive it is to the stability of the particle surface.
[0068] In addition, Ni 2+ With Li + It is easy to mix up. The reason is that Ni 2+ With Li + The radius of Ni 2+ Easier migration to Li + The vacancies formed by the insertion and removal of Li lead to the precipitation of Li. During the repeated charge and discharge process, Ni 2+ With Li + The mixing ratio of Li + The intercalation and deintercalation in the layered structure of the ternary material becomes increasingly difficult, which eventually leads to the deterioration of the cycle performance of the secondary battery. The presence of Co can effectively stabilize the layered structure of the ternary material and inhibit the mixing of lithium and nickel. Therefore, adjusting the nickel content in the particle surface and vicinity of the ternary positive electrode active material to be relatively low and the cobalt content to be relatively high is conducive to improving the stability of the material and improving the cycle performance of the secondary battery.
[0069] The present application does not particularly limit the overall content of nickel in the positive electrode active material, and the gradient change rate. According to some embodiments, the positive electrode active material may contain any suitable nickel content, in particular a low nickel content, or a medium nickel content. The gradient change rate of the nickel content in the positive electrode active material may be that the nickel content in a certain area inside the particle is relatively uniform, and in the area on the surface of the particle and nearby areas, the nickel content gradually decreases from the inside of the particle to the surface. For example, it may be an area extending from the surface of the particle along the radial direction of the particle to the inside within a range of L, where L = 1.5 μm, 1 μm or 0.5 μm. In some embodiments, the nickel content may be gradually reduced from the center of the particle to the surface of the particle.
[0070] In the embodiment of the present application, the mass concentration of Co gradually increases from the inside of the particle to the surface of the particle along the radial direction of the particle, while the mass concentration of Ni gradually decreases. Under the premise of a low-cost metal ratio in which the overall Ni / Co content in the material remains unchanged, the concentrations of cobalt and nickel at different positions in the particle show a gradient change, thereby reducing the Ni content in the surface layer and increasing the Co content in the surface layer. This can provide a positive electrode active material with high structural stability and good power performance under high voltage.
[0071] Similarly, in the embodiments of the present application, since there is no obvious core-shell structure, there is no sudden change in the concentration of any element from the interior of the particle to the surface of the particle, which helps to obtain a positive electrode active material with better performance stability.
[0072] In some embodiments, the absolute value of the difference in mass concentration of Li and Mn at any two points in the particle is less than or equal to 20%.
[0073] In the present application, the mass concentration of Li and Mn at any two points in the particle is the mass concentration of Li and Mn in all elements within the extremely small volume of the two points. In the present application, the difference in mass concentration of Li and Mn at any two points in the particle is less than or equal to 20%, which means that the distribution uniformity of Li and Mn in the particle is relatively high. Optionally, the difference in mass concentration of Li and Mn at any two points in the particle is less than or equal to 15%, less than or equal to 10%, or even less than or equal to 5%. The uniform distribution of Li and Mn elements can better exert the performance improvement effect of Li and Mn elements on the positive electrode active material. In addition, lithium ions located in different areas inside the particle can also obtain more consistent migration and diffusion capabilities within the uniform structure of the Mn element.
[0074] Without being bound by existing theories, it is speculated that the relatively uniform distribution of Li and Mn elements in the particles may be due to the fact that their migration ability is stronger than that of Ni and Co elements during the sintering process.
[0075] In some embodiments, the positive electrode active material is represented by the following Formula 1:
[0076] Li x (Ni a Co b Mn c ) d M 1-d O 2-y A y Formula 1
[0077] Among them, 0.95≤x≤1.3, 0.3≤a≤0.7, 0.01≤b≤0.15, 0.1≤c≤0.5, a+b+c=1, 0.95≤d≤1, 0≤y≤0.1, M includes at least one selected from Zr, Sr, B, Ti, Mg, Sn, Tb, W, Nb and Al, and A includes at least one selected from S, N, F, Cl, Br and I.
[0078] It should be noted that in the present application, the chemical formula of the lithium nickel manganese oxide material is the chemical formula of the material used in the battery preparation process. In the positive electrode plates, battery cells, and electrical equipment, due to the processes of formation and circulation, those skilled in the art can understand that the elements in the above chemical formula may be lost. For example, in the positive electrode plates, battery cells, and electrical equipment, due to the processes of circulation, the oxygen element in the positive electrode active material is lost, so the measured oxygen element content in the positive electrode active material will be reduced. In addition, due to the processes of formation and circulation, lithium ions will be consumed in the positive electrode plates, battery cells, and electrical equipment, so the measured lithium element content in the positive electrode active material will be reduced. At the same time, if the positive electrode plates and negative electrode plates are supplemented with lithium, after the processes of formation and circulation, the measured lithium element content in the positive electrode active material will increase.
[0079] In some embodiments, the amount of Li in the above formula 1 is represented by the value of x. Optionally, the value of x can be 0.95, 0.98, 1.0, 1.1, 1.2, or 1.3.
[0080] In the above formula 1, the amounts of Ni, Co and Mn are represented by the values of a, b and c, respectively. Optionally, 0.5≤a≤0.65, 0.05≤b≤0.12, 0.95≤d≤0.99, the value of a can be 0.3, 0.4, 0.5, 0.6, 0.7; the value of b can be 0.04, 0.06, 0.08, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15; the value of c can be 0.1, 0.2, 0.3, 0.4, 0.5. As described above, the mass concentration of the cobalt element in the region close to the surface of the particles of the positive electrode active material varies in a gradient, so that the Co content is higher on the surface of the particles, while the Co content inside the particles is relatively low. Therefore, the positive electrode active material of the present application can still obtain improved structural stability and power performance at high voltage with a reduced Co content (0.01≤b≤0.15, optionally 0.05≤b≤0.12).
[0081] In addition, the mass concentration of nickel in the region near the surface of the particles of the positive active material is also gradient, so that the Ni content is low on the particle surface, while the Ni content inside the particle is relatively high. Therefore, the positive active material of the present application can be suitable for the design of low nickel content to medium nickel content (0.3≤a≤0.7, optional 0.5≤a≤0.65) under the condition of improving the stability of the particle surface, so as to have an ideal gram capacity.
[0082] In the above formula 1, M is a doping element. In the present application, the positive electrode active material may not contain the doping element M. A preferred embodiment is that the positive electrode active material contains the doping element M. By doping the M element, oxygen atoms can be effectively bound, so that the positive electrode active material is not prone to oxygen release during high temperature cycling and high temperature storage, and the structural stability of the positive electrode active material is significantly improved. In some embodiments, the M element can be selected from at least one of Zr, Sr, W, Na, Mg, F, P, etc., or a combination thereof.
[0083] The doping amount of the M element is represented by the value of (1-d). Optionally, 0.95≤d≤0.99. The value of d can be 0.95, 0.96, 0.97, 0.98, 0.99.
[0084] In the above formula 1, A is also a doping element. In the present application, the positive electrode active material may not contain the doping element A, or may contain the doping element A. By doping the element A, the structural stability of the positive electrode active material can be further improved, and the side reactions on the particle surface can be reduced, thereby further improving the cycle performance of the battery.
[0085] The doping amount of element A is represented by the value y. Optionally, 0.02≤y≤0.1. The value of y can be 0.02, 0.05, 0.07, 0.09, 0.1.
[0086] In the present application, the concentration of a certain element in the positive electrode active material can be obtained by EDX (Energy Dispersive X-Ray Spectroscopy) or EDS element analysis combined with TEM (Transmission Electron Microscope) or SEM (Scanning Electron Microscope) single-point scanning test element concentration distribution or other similar methods. When EDX or EDS element analysis is combined with TEM or SEM single-point scanning test, taking Li element as an example, the mass concentration of Li element in μg / g at different sites in the particle is recorded as η 1 , η 2 , η 3 ,…,η n , n is a positive integer greater than or equal to 15.
[0087] The average mass concentration of Li in the particles is the mass concentration of Li in all elements within a single particle, which can be obtained by EDX or EDS element analysis combined with TEM or SEM surface scanning test element concentration distribution or other similar methods. When testing by EDX or EDS element analysis combined with TEM or SEM surface scanning test element concentration distribution, the test surface includes all points in the above single point test. The average mass concentration of Li in the particles is recorded as The unit is ppm (ie, parts per million by mass, μg / g).
[0088] Similarly, the average mass concentrations of Ni, Co, Mn, M element, and A element in the particles can be measured and calculated using the above method.
[0089] The mass concentration deviation σ of the Li element at any point in the particle is calculated according to the following formula (1):
[0090]
[0091] It can be understood that the mass concentration deviation of the Mn element between any two points in the particle can also be obtained by using the above-mentioned test and calculation method.
[0092] Similarly, the average mass concentration of Co or Ni in a certain area of the particle, or the mass concentration at a certain point, can be obtained by the above test and calculation method. From this, it can be calculated that the Co mass concentration on the surface of the particle is a multiple of the Co mass concentration at a distance L=1 μm extending inward along the radial direction of the particle.
[0093] In some embodiments, the volume distribution particle size Dv50 of the particles is in the range of 3.5 μm≤Dv50≤7.5 μm, optionally, 4 μm≤Dv50≤7 μm.
[0094] In this application, the volume distribution particle size Dv50 of the particles of the positive electrode active material has a well-known meaning in the art, which respectively represents the particle size corresponding to when the cumulative volume distribution percentage of the material reaches 50%, and can be measured using instruments and methods known in the art. For example, it can be measured with a laser particle size analyzer with reference to GB / T 19077-2016. The test instrument can be a Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.
[0095] Here, the value of the volume distribution particle size range of the particles can be the two end points or any value between the two end points, for example, it can be: 3.5μm, 3.7μm, 3.9μm, 4μm, 4.1μm, 4.2μm, 4.3μm, 4.5μm, 4.7μm, 4.9μm, 5μm, 5.1μm, 5.3μm, 5.5μm, 5.7μm, 5.9μm, 6μm, 6.1μm, 6.3μm, 6.5μm, 6.7μm, 7μm, 7.2μm, 7.3μm, 7.5μm, etc.
[0096] When the volume distribution particle size of the particles is within the above range, the smaller the particle size, the better the electronic conductivity and ion transport, thereby further reducing the impedance of the secondary battery and improving the power performance and kinetic performance.
[0097] In some embodiments, the positive electrode active material further has a coating layer. Optionally, the coating layer is an oxide or hydroxide of M', wherein M' includes at least one selected from Mg, Al, Ca, Ba, Ti, Zr, Zn, Nb, Sb, Ce, La, W and B. Optionally, M' includes at least one selected from Al, Ti, Zr, Nb, W.
[0098] In the present application, by coating and modifying the surface of the particles of the positive electrode active material, the particle material can be effectively protected, making the interface of the particles more stable, and effectively reducing the phase change of the surface structure. In addition, the presence of the coating layer can also effectively protect the surface of the positive electrode active material from being corroded by the electrolyte, reduce side reactions, improve the material's anti-gas production performance, reduce the gas production of the battery, and improve the battery's cycle performance.
[0099] In some embodiments, the coating layer has a thickness of 0.001-0.5 μm, and optionally 0.01-0.1 μm.
[0100] Here, the value of the coating thickness can be the two end points or any value between the two end points, for example, it can be: 0.005μm 0.01μm, 0.015μm, 0.02μm, 0.025μm, 0.03μm, 0.035μm, 0.04μm, 0.045μm, 0.05μm, 0.055μm, 0.06μm, 0.065μm, 0.07μm, 0.075μm, 0.080μm, 0.085μm, 0.09μm, 0.095μm, 0.1μm, 0.2μm, 0.3μm, 0.4μm, 0.5μm.
[0101] In the present application, by controlling the thickness of the coating layer within the above range, the contact between the electrolyte and the bulk particles can be effectively isolated, side reactions can be reduced, and lithium ions can have a higher diffusion and migration ability in the positive electrode active material.
[0102] The present application also provides a method for preparing the above-mentioned positive electrode active material, the preparation method comprising:
[0103] S1: mixing a lithium salt, hydroxides of Ni, Co and Mn as precursors and an optional compound containing a doping element M and performing a first sintering to obtain initial material particles;
[0104] S2: mixing the starting material particles with a cobalt-containing compound and performing a second sintering to obtain particles containing lithium nickel cobalt manganese oxide.
[0105] The preparation method of the positive electrode active material of the present application first prepares the initial material particles with the target composition by the first sintering, and then performs the second sintering with the cobalt-containing compound, thereby obtaining the positive electrode active material with the above characteristics, wherein the mass concentration of Co gradually decreases from the inside of the particle to the surface of the particle along the radial direction of the particle within the range of L=1μm extending from the surface of the particle to the inside of the particle. In addition, the particle does not have an obvious core-shell structure, and the mass concentration of the Co element (and other elements) in the particle does not have a sudden obvious interface, but is an integrated crystal particle, especially a single crystal particle.
[0106] During the second sintering process, the cobalt-containing compound is coated on the surface of the initial material particles, so that the Co content in the initial material particles is lower than that on the surface, and the Co ions diffuse from the particle surface to the bulk phase. From the particle surface to a certain depth inside, the Co content shows a gradual decreasing trend without a sudden change. Thus, the positive electrode active material is obtained.
[0107] In S1, a lithium source, precursors of Ni, Co and Mn, and optionally a compound containing a doping element M and a compound containing a doping element A are mixed and first sintered to obtain initial material particles.
[0108] As an example of preparing particles containing the initial material, lithium salt, hydroxides of Ni, Co and Mn as precursors, and, if any, a compound containing the M element and / or a compound containing the A element are placed in, for example, a ball mill mixer or a high-speed mixer and mixed. The mixing time can be, for example, 0.5-3 hours.
[0109] The present application has no particular limitation on the lithium source used in the first sintering. For example, the lithium source may be lithium oxide (Li 2 O), lithium phosphate (Li 3 PO 4), lithium dihydrogen phosphate (LiH 2 PO 4 ), lithium acetate (CH 3 COOLi), lithium hydroxide (LiOH), lithium carbonate (Li 2 CO 3 ) and lithium nitrate (LiNO 3 ). Further, the lithium source is one or more of lithium carbonate, lithium hydroxide and lithium nitrate; further, the lithium source is lithium carbonate.
[0110] The present application also has no particular restrictions on the precursors of Ni, Co and Mn used in the first sintering. For example, the precursor is one or more of oxides, hydroxides and carbonates containing Ni, Co and Mn, for example, hydroxides containing Ni, Co and Mn. The precursor can be prepared by any method. For example, it can be prepared by coprecipitation, gel method or solid phase method, but is not limited thereto.
[0111] In some embodiments, the precursor is prepared by coprecipitation. The following uses coprecipitation as an example to illustrate the preparation method of obtaining hydroxide precursors of Ni, Co and Mn.
[0112] A Ni source, a Co source and a Mn source are dispersed in a solvent to obtain a mixed solution; the mixed solution, a strong alkali solution and a complexing agent solution are simultaneously pumped into a stirred reactor in a continuous parallel flow reaction mode, the pH value of the reaction solution is controlled to be 10-13, the temperature in the reactor is 25°C-90°C, and an inert gas is passed during the reaction process for protection; after the reaction is completed, the hydroxide containing Ni, Co and Mn is obtained through aging, filtration, washing and vacuum drying.
[0113] The Ni source is a soluble nickel salt. For example, the Ni source is one or more of nickel sulfate, nickel nitrate, nickel chloride, nickel oxalate and nickel acetate. Optionally, the Ni source is one or more of nickel sulfate and nickel nitrate, and further is nickel sulfate.
[0114] The Co source is a soluble cobalt salt, such as one or more of cobalt sulfate, cobalt nitrate, cobalt chloride, cobalt oxalate and cobalt acetate. Optionally, the Co source is one or more of cobalt sulfate and cobalt nitrate, further cobalt sulfate.
[0115] The Mn source is a soluble manganese salt, such as one or more of manganese sulfate, manganese nitrate, manganese chloride, manganese oxalate and manganese acetate. Optionally, the Mn source is one or more of manganese sulfate and manganese nitrate, and further manganese sulfate.
[0116] The strong base is one or more of LiOH, NaOH and KOH.
[0117] The complexing agent is one or more of ammonia water, ammonium sulfate, ammonium nitrate, ammonium chloride, ammonium citrate and disodium ethylenediaminetetraacetate (EDTA), such as ammonia water.
[0118] There is no particular restriction on the solvents of the mixed solution, the strong base solution and the complexing agent solution. For example, the solvents of the mixed solution, the strong base solution and the complexing agent solution are each independently one or more of deionized water, methanol, ethanol, acetone, isopropanol and n-hexanol, such as deionized water.
[0119] The inert gas introduced during the reaction is, for example, one or more of nitrogen, argon, and helium.
[0120] In some embodiments, the molar ratio of Ni:Co:Mn in the precursor is in the range of (50-70):(6-25):(29-40), optionally, in the range of (55-65):(6-12):(29-33).
[0121] By controlling the molar ratio of Ni:Co:Mn in the precursor to be within the above range, it is helpful to achieve the above-mentioned excellent performance of the positive electrode active material.
[0122] In some embodiments, the positive electrode active material includes a doping element M. In the embodiment, during the first sintering, a compound containing the doping element M is added. The doping element M is as defined above. The compound containing the doping element M is one or more of an oxide, nitrate, carbonate, bicarbonate, sulfate, chloride, hydroxide and acetate of the M element. Those skilled in the art can determine a suitable compound containing the M element based on the selected M element.
[0123] In some embodiments, the positive electrode active material further comprises a doping element A. In the embodiment, during the first sintering, a compound comprising the doping element A is added. The doping element A is as defined above. The compound comprising the doping element A is one or more of an ammonium salt and a lithium salt of the element A, for example, NH 4 F. NH 4 Cl, NH 4 Br, (NH 4 ) 2 S, LiF, LiCl, LiBr and Li 2 One or more of S.
[0124] The lithium source, the precursors of Ni, Co and Mn and the optional compound containing the doping element M and the compound containing the doping element A may be mixed according to the stoichiometric ratio of each element shown in Formula 1 above and subjected to a first sintering.
[0125] In some embodiments, the first sintering is carried out at 600° C.-1000° C. for 5 h to 25 h, and optionally at 650° C.-950° C. for 8 h to 20 h.
[0126] The first sintering temperature may be an end point value or any value between the end points, for example, it may be 600°C, 620°C, 650°C, 670°C, 700°C, 720°C, 750°C, 780°C, 800°C, 820°C, 850°C, 880°C, 900°C, 920°C, 950°C, 980°C, 1000°C, etc. The holding time of the first sintering temperature may be an end point value or any value between the end points, for example, it may be 5h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 22h, 25h, etc.
[0127] After the first sintering, the sintered material was cooled to room temperature and then ground for 5 hours to obtain initial material particles.
[0128] The process conditions of the first sintering are substantially the same as those of the conventional ternary positive electrode active material preparation.
[0129] In S2, the starting material particles are mixed with a cobalt-containing compound and subjected to a second sintering to obtain particles containing lithium nickel cobalt manganese oxide.
[0130] For example, the obtained starting material particles can be mixed with the cobalt-containing compound in, for example, a high-speed mixer.
[0131] The cobalt-containing compound may be any one or more of the above-mentioned cobalt sources, which will not be described in detail here.
[0132] In some embodiments, the ratio of the amount of the cobalt-containing compound in terms of cobalt element to the mass of the particles containing lithium nickel cobalt manganese oxide is in the range of 2000-10000 ppm, optionally, 4000-7000 ppm. The above ratio range refers to the range of the amount of the cobalt-containing compound added when mixed with the initial material particles. Specifically, the amount of the cobalt-containing compound added in the above range is calculated according to the mass (in μg) of the cobalt-containing compound required to be added relative to 1g of the particles containing lithium nickel cobalt manganese oxide finally obtained.
[0133] Here, the amount of the cobalt-containing compound, in terms of the ratio of the mass of the cobalt element to the mass of the particles containing lithium nickel cobalt manganese oxide, can be either end points or any value between the end points, for example, 2200ppm, 2500ppm, 2800ppm, 3000ppm, 3200ppm, 3500ppm, 3800ppm, 4000ppm, 4200ppm, 4500ppm, 4800ppm, 5000ppm, 5500ppm, 6000ppm, 6500ppm, 7000ppm, 7200ppm, 7500ppm, 8000ppm, 8200ppm, 8500ppm, 9000ppm, 9500ppm, 9800ppm, 10000ppm, etc.
[0134] By controlling the addition amount of the cobalt-containing compound within the above range, the surface layer and the vicinity of the obtained particle material can have an ideal Co mass concentration and a good concentration gradient, thereby achieving the excellent performance of the above-mentioned positive electrode active material.
[0135] In some embodiments, the second sintering is carried out at 650° C.-800° C. for 5 h-7 h.
[0136] Exemplarily, the value of the second sintering temperature can be the two end points, or any value between the two end points, for example, it can be: 650°C, 660°C, 670°C, 680°C, 690°C, 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, 790°C, 800°C, etc. The holding time of the second sintering temperature (also called the second sintering time) can be the two end points, or any value between the two end points, for example, it can be: 5h, 5.5h, 6h, 6.5h, 7h, etc.
[0137] Through the second sintering, the cobalt-containing compound coated on the surface of the initial material particles and the initial material particles become integrated particles. Since the cobalt content of the particle surface is higher than that of the initial material particles, the cobalt element gradually diffuses into the initial material particles during the second sintering to form a material particle with a high surface Co content, and a gradually decreasing Co content in the radial direction of the surface pointing to a certain depth inside the particle, thereby helping to obtain a positive electrode active material with high structural stability and good power performance.
[0138] In order to avoid the situation where the Co content in the surface layer of the particles finally obtained tends to be consistent, the second sintering temperature should not be too high, and the sintering time should not be too long. At the same time, the second sintering temperature should not be too low, and the sintering time should not be too short, so as to prevent the cobalt-containing compound from failing to completely form an integrated single crystal particle with the initial material particles. Within the range of the above-mentioned second sintering temperature and the second sintering time, the final integrated particle containing lithium nickel cobalt manganese oxide can be obtained, and the surface layer of the particle has an ideal Co content, and within the range of a certain distance extending from the particle surface along the radial direction of the particle to the particle interior, the mass concentration of Co gradually increases along the radial direction of the particle from the particle interior to the particle surface.
[0139] At the same time, some of the Ni and Mn elements in the initial material particles will diffuse to the surface of the final lithium nickel cobalt manganese oxide particles. Since only cobalt-containing compounds are further added in the second sintering, the Ni content in the surface layer and nearby areas of the final particles will gradually decrease from the inside of the particles to the surface. The Mn element may have a relatively uniform distribution in the particles due to its strong element migration ability.
[0140] In some embodiments, the second sintering is performed in an oxygen-rich atmosphere. Optionally, the oxygen-rich atmosphere has a volume ratio of air:oxygen between (0:10) and (8:2).
[0141] Here, the volume ratio of air:oxygen can be two end point values, or any value between the two end point values, for example, it can be: 0:10, 1:9, 2:8, 3:7, 4:6, 5:6, 6:4, 8:2, etc.
[0142] In the present application, the second sintering is carried out in an oxygen-rich sintering atmosphere, which helps to suppress the Li / Ni mixing caused by low cobalt during the sintering process, can extend the life of the material, and help improve the cycle life of the secondary battery.
[0143] In some embodiments, the preparation method further comprises: mixing the particles containing lithium nickel cobalt manganese oxide with an M' source and performing a third sintering to form a coating layer on the surface of the particles. Optionally, the M' comprises at least one selected from Mg, Al, Ca, Ba, Ti, Zr, Zn, Nb, Sb, Ce, La, W and B.
[0144] The present application has no particular restrictions on the source of M'. For example, the source of M' may be one or more of chlorides, sulfates, nitrates, oxides, hydroxides, fluorides, carbonates, bicarbonates, acetates, phosphates, dihydrogen phosphates and organic compounds of the above elements, but is not limited thereto. Those skilled in the art can determine a suitable compound as the source of M' according to the selected M element.
[0145] In this embodiment, the amount of the compound used as the M' source added relative to the final positive electrode active material is 100ppm to 3000ppm, such as 100ppm, 300ppm, 400ppm, 700ppm, 1000ppm, 1300ppm, 1500ppm, 1800ppm, 2000ppm, 2200ppm, 2500ppm, 2700ppm, 3000ppm, etc. The amount of the compound used as the M' source added within the above range can make the final coating layer have the above suitable thickness, thereby better isolating the particle body from the electrolyte, reducing the positive electrode side reaction, and ensuring that the positive electrode active material has a good lithium ion diffusion and migration ability.
[0146] In some exemplary embodiments, performing the third sintering operation includes: uniformly mixing the particles of lithium nickel cobalt manganese oxide obtained in the second sintering process with the compound as the M' source, sintering at a temperature of 250° C. to 350° C., and keeping the temperature for 4 to 6 hours to obtain positive electrode active material particles having a coating layer of M' oxide. Due to the low sintering temperature, the M' element is not easy to diffuse into the interior of the main body particles, and the elements in the main body particles are not easy to diffuse further.
[0147] The present application also provides a secondary battery and an electrical device.
[0148] The secondary battery and the electric device of the present application will be described below with reference to the drawings as appropriate.
[0149] In one embodiment of the present application, a secondary battery is provided.
[0150] The term "secondary battery" mentioned herein refers to a battery cell, a battery module or a battery pack, which are described below.
[0151] Typically, a secondary battery cell includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator. During the battery charge and discharge process, active ions (i.e., lithium ions) are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0152] Positive electrode
[0153] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, and the positive electrode film layer includes the positive electrode active material of the present application.
[0154] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0155] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0156] The positive electrode active material of the secondary battery of the present application includes at least the above-mentioned positive electrode active material of the present application. In some embodiments, the positive electrode active material may also include positive electrode active materials for lithium-ion batteries known in the art. As an example, the positive electrode active material may also include at least one of the following materials: lithium-containing phosphates with an olivine structure, lithium transition metal oxides and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxides (such as LiCoO 2 ), lithium nickel oxide (such as LiNiO 2 ), lithium manganese oxide (such as LiMnO 2 、LiMn 2 O 4 ), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 (Also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O 2 (Also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O 2 (Also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O 2(Also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O 2 (Also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O 2 ) and its modified compounds, etc. Examples of lithium phosphates containing olivine structures may include, but are not limited to, lithium iron phosphate (such as LiFePO 4 (also referred to as LFP), composite materials of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO 4 ), at least one of a composite material of lithium manganese phosphate and carbon, a composite material of lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
[0157] The battery will be accompanied by Li deintercalation and consumption during the charge and discharge process, and the molar content of Li is different when the battery is discharged to different states. In the list of positive electrode active materials in this application, the molar content of Li is the initial state of the material, that is, the state before feeding. The positive electrode active material is used in the battery system, and the molar content of Li will change after charge and discharge cycles.
[0158] In the list of positive electrode active materials in this application, the molar content of O is only a theoretical value. The release of oxygen from the lattice will cause the molar content of oxygen to change, and the actual molar content of O will fluctuate.
[0159] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0160] In some embodiments, the positive electrode film layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0161] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0162] Negative electrode
[0163] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.
[0164] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0165] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0166] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0167] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0168] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0169] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0170] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0171] Electrolytes
[0172] The electrolyte plays a role in conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid.
[0173] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0174] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0175] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0176] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0177] Isolation film
[0178] In some embodiments, the battery cell further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0179] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0180] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0181] In some embodiments, the battery cell may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.
[0182] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0183] The present application has no particular limitation on the shape of the battery cell, which may be cylindrical, square or any other shape. Figure 3 The battery cell 5 is a square structure as an example.
[0184] In some embodiments, reference Figure 4 , the outer packaging may include a shell 51 and a top cover assembly 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the top cover assembly 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0185] In some embodiments, battery cells may be assembled into a battery module. The number of battery cells contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0186] Figure 5 4 is an example of a battery module. Figure 5 In the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.
[0187] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.
[0188] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0189] Figure 6 and Figure 7 1 is a battery pack 1 as an example. Figure 6 and Figure 7 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0190] In addition, the present application also provides an electric device, which includes a secondary battery provided in the present application. The secondary battery can be used as a power source for the electric device, or as an energy storage unit for the electric device. The electric device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0191] As the electrical device, a battery cell, a battery module or a battery pack can be selected according to its usage requirements.
[0192] Figure 8 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.
[0193] As another example, the device may be a mobile phone, a tablet computer, a notebook computer, etc. The device is usually required to be light and thin, and a battery cell may be used as a power source.
[0194] Example
[0195] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0196] Example
[0197] Preparation of positive electrode active materials
[0198] Example 1
[0199] Preparation of positive electrode active material precursor: In a continuous stirred tank reactor, nickel sulfate, manganese sulfate, and cobalt sulfate were added to deionized water in a molar ratio of Ni:Co:Mn=55:6:39 (based on each element) to prepare a transition metal salt solution with a total molar concentration of 2 mol / L. 4 mol / L sodium hydroxide was added as a precipitant and 0.4 mol / L ammonia water was added as a complexing agent. The precursor Ni was prepared by coprecipitation reaction at pH 11.3 for 24 hours. 0.55 Co 0.06 Mn 0.39 (OH) 2 .
[0200] Preparation method of positive electrode active material:
[0201] Step S1: The above precursor and lithium carbonate (as a Li-containing compound) are mixed at a molar ratio of 1:1.07, and 1000 ppm of Al is added as Al element. 2 O 3 , calculated as W element, 2000ppm of WO 3 The mixture was mixed in a high-speed mixer, and then sintered in a kiln at 900°C for 12 hours. After cooling to room temperature, the mixture was mechanically ground by a jet mill for 5 hours to obtain product N1.
[0202] Step S2: The product N1 obtained in the previous step is reacted with 4000 ppm (in terms of cobalt element) of Co(OH) 2 The mixture is placed in a high-speed mixer for mixing, and then placed in a kiln for sintering at 700°C for 6 hours to obtain product N2. After high-temperature sintering, metal ions diffuse to form a structure with a high Co content on the surface and a low Co content at a certain depth inside.
[0203] Step S3: The product N2 obtained in step S2 is mixed with 2000ppm TiO 2 After uniform mixing, sintering was performed at 300° C. for 5 h to obtain the single crystal positive electrode active material of the present application. The Dv50 of the single crystal positive electrode active material is about 4 μm. The stoichiometric formula of the product N1 is shown in Table 1.
[0204] Example 2-26
[0205] The positive electrode active materials of each embodiment were prepared in a similar manner to that of embodiment 1. The changed material composition, raw material dosage, and preparation process conditions are shown in Table 1. The contents not listed in Table 1 are the same as those of embodiment 1. In these embodiments, the Dv50 of the obtained positive electrode active materials is about 4 μm.
[0206] Comparative Example 1
[0207] Referring to the preparation method of the positive electrode active material of Example 1, the difference is that the preparation process of step S2 is omitted. The Dv50 of the obtained positive electrode active materials is about 4 μm.
[0208] Comparative Example 2
[0209] Referring to the preparation method of the positive electrode active material of Example 1, the difference is that the preparation process of step S2 and step S3 is omitted. The Dv50 of the obtained positive electrode active materials is about 4 μm.
[0210] Preparation of lithium-ion batteries
[0211] Preparation of positive electrode sheet: The positive electrode active materials of Examples 1-26 and Comparative Examples 1-2 prepared above, the conductive carbon black SP and the binder PVDF were dispersed in the solvent NMP at a weight ratio of 98:1:1 and mixed evenly to obtain positive electrode slurry. The positive electrode slurry was evenly coated on the positive electrode current collector aluminum foil, and after drying and cold pressing, a positive electrode sheet was obtained, and the coating amount per unit area was 0.27g / 1540.25mm 2 .
[0212] Preparation of negative electrode materials: Mix the negative electrode active material graphite, thickener sodium carboxymethyl cellulose, adhesive styrene butadiene rubber, and conductive agent acetylene black in a mass ratio of 97:1:1:1, add deionized water, and obtain negative electrode slurry under the action of a vacuum mixer. The negative electrode slurry is evenly coated on the copper foil, dried at room temperature, transferred to a 120°C oven for drying for 1 hour, and then supercooled and cut to obtain the negative electrode sheet. The coating amount per unit area is 0.17g / 1540.25mm 2 .
[0213] Preparation of electrolyte: The organic solvent is a mixed solution containing ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC), wherein the volume ratio of EC, EMC and DEC is 20:20:60. In an argon atmosphere glove box with a water content of <10ppm, fully dried lithium salt (lithium hexafluorophosphate) is dissolved in the above organic solvent and mixed evenly to obtain an electrolyte. The concentration of the lithium salt is 1 mol / L.
[0214] Isolation film: Use 12μm thick polypropylene isolation film.
[0215] Preparation of lithium-ion batteries: stack the positive electrode sheet, separator and negative electrode sheet prepared above in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wind them into a square bare battery cell, put them into an aluminum-plastic film, and then bake them at 80°C to remove water, inject the electrolyte prepared above, seal them, and obtain a finished battery after processes such as formation and capacity division.
[0216] Performance Testing
[0217] The following tests were performed on the positive electrode active materials and batteries obtained in the above examples and comparative examples.
[0218] 1. X-ray Photoelectron Spectroscopy (XPS)
[0219] The positive electrode active material prepared in Example 1 was analyzed on the surface and inside using Shimadzu's Axis Supra+ X-ray photoelectron spectroscopy. For specific test results, please refer to Figure 2 In order to determine the internal conditions of the positive electrode active material, before performing the X-ray photoelectron spectroscopy analysis operation, the positive electrode active material prepared in Example 1 can be cut using argon ion polishing technology to remove the outer layer material of a predetermined thickness (500nm, 1000nm and 2000nm).
[0220] The positive electrode active materials prepared in Example 5 and Example 6 were subjected to surface analysis using Shimadzu's Axis Supra+ X-ray photoelectron spectroscopy. For specific test results, please refer to Figure 2 shown.
[0221] The same method is used to perform surface and internal analysis on the positive electrode active materials prepared in Example 3 and Example 8. Similarly, in order to determine the internal conditions of the positive electrode active materials, before performing the X-ray photoelectron spectroscopy analysis operation, the positive electrode active materials prepared in Example 3 and Example 8 can be cut using argon ion polishing technology to remove the outer layer material of a predetermined thickness and obtain the conditions at 1000 nm (1 μm) from the surface.
[0222] By calculating the peak area of the curves obtained in Example 1, Example 3 and Example 8 at 777.8 ev (dividing the peak area at the surface by the peak area at 1000 nm), the ratio of the Co mass concentration on the surface of the positive electrode active material particle to the Co mass concentration at a distance L = 1 μm extending radially into the interior of the particle is obtained.
[0223] In Example 1, the ratio of the Co mass concentration on the surface of the positive electrode active material particle to the Co mass concentration at a distance L=1 μm extending radially toward the interior of the particle is 1.5; in Example 3, the ratio of the Co mass concentration on the surface of the positive electrode active material particle to the Co mass concentration at a distance L=1 μm extending radially toward the interior of the particle is 1.2; in Example 8, the ratio of the Co mass concentration on the surface of the positive electrode active material particle to the Co mass concentration at a distance L=1 μm extending radially toward the interior of the particle is 1.6.
[0224] 2. Battery capacity in grams
[0225] The soft pack battery was placed in a constant temperature environment of 25°C for 2 hours, then charged to 4.5V at 1 / 3C at 2.8V~4.5V, then charged at a constant voltage at 4.5V to a current ≤0.05mA, placed for 5 minutes, and then discharged to 2.8V at 1C, and the capacity C of the battery was recorded. 放 The gram capacity of the battery is calculated according to the following formula.
[0226] Gram capacity = battery capacity C 放 (mAh) / mass of positive electrode active material (g).
[0227] 3. DC resistance (DCR)
[0228] Place each lithium-ion battery prepared above at room temperature until thermal equilibrium is reached. Perform three standard charge and discharge cycles at a current of 1 / 3C, with a cut-off voltage of 4.5V, and record the capacity of the battery at the third standard charge and discharge cycle as the standard capacity C. Place at a test temperature of 25°C until thermal equilibrium is reached. Charge the battery to 50% SOC at a discharge rate of 1 / 3C and discharge at a current rate of 1C for 30S. Record the battery voltage V2 before discharge termination, the current I, and the battery voltage V1 after the battery voltage stabilizes. Calculate according to the formula DCR = (V2-V1) / I to obtain the DC internal resistance DCR.
[0229] 4. Cycle performance test
[0230] Under the test environment of 25℃, the battery was charged and discharged; it was charged to 4.5V with a constant current and constant voltage at 1 / 3C current, left to stand for 10 minutes, and then discharged to 2.8V with a constant current at 1C current. The final result is expressed as the corresponding number of cycles when the 0.33C / 1C cycle charge and discharge capacity decays to 80%.
[0231] The test results of items 2-4 of lithium ions prepared by the above embodiments and comparative examples are shown in Table 1 below:
[0232]
[0233] As can be seen from Table 1 above, compared with the positive electrode active materials of Comparative Example 1 (with a coating layer) and Comparative Example 2 (without a coating layer) without the second sintering, Examples 1-26, especially compared with Example 1, the positive electrode active materials of the present application have achieved significant improvements in the power performance (DC resistance DCR decreases) and cycle performance of the secondary battery. In addition, the gram capacity of the positive electrode active materials has also been improved.
[0234] Specifically, in Examples 7-12, in the second sintering, Co(OH) 2 The positive electrode active materials obtained by different addition amounts are all helpful to increase the gram capacity of the battery, reduce impedance and improve the cycle performance. Preferably, the cobalt-containing compound is added in an amount of 4000-7000ppm based on the Co element to achieve the best balance of various properties. If the addition amount is too low, the improvement of the kinetic performance is limited, while if the addition amount is too high, on the one hand, the cost is increased, and on the other hand, too high an addition amount is prone to the phenomenon of material structure destruction due to Co dissolution during the cycle, resulting in deterioration of material performance, which is not conducive to improving the cycle performance.
[0235] Different second sintering temperatures are used in Examples 13-16. From Examples 13-14 and comparison with Example 1, it can be seen that using a temperature of about 650-800°C for the second sintering helps to improve the gram capacity of the material and the cycle performance of the secondary battery. If the second sintering temperature is too low, the sintering effect is poor, the Co element is enriched in the surface layer of the material, and an ideal gradient cannot be formed, which is not conducive to the improvement of the kinetics of the secondary battery. If the sintering temperature is too high, the Co on the surface of the material diffuses into the bulk phase, resulting in insufficient Co content on the surface of the material, which is not conducive to the improvement of the cycle performance.
[0236] In Examples 17-20, different second sintering times were used. From Examples 17-18 and Example 1, it can be seen that a second sintering time of 6-7h is more advantageous and helps to improve both the power performance and cycle performance of the secondary battery. If the second sintering time is too short, the Co element will not migrate enough and will be mostly enriched in the surface layer of the material, while if it is too long, the Co content in the surface layer of the material will be insufficient, so the kinetic performance of the secondary battery cannot be significantly improved.
[0237] In Example 1-4, the ratio of Ni, Co, and Mn in the precursor is changed. As the ratio of Co increases, the secondary battery can have a significantly reduced DC impedance, indicating that the power performance of the secondary battery is significantly improved. In addition, the cycle performance is also improved.
[0238] In Examples 5 and 6, the power performance and cycle performance of the secondary battery are affected to a certain extent by reducing the addition amount of the doping elements Al and W compared with Example 1.
[0239] In addition, the oxygen content in the second sintering was adjusted in Examples 24-26. The introduction of oxygen can reduce the mixing of lithium and nickel in the material, help obtain a more stable bulk structure, and achieve improved cycle performance. When the oxygen content is increased (Examples 24 and 25), the cycle performance of the secondary battery is significantly improved.
[0240] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A positive electrode active material comprising particles containing lithium nickel cobalt manganese oxide, characterized in that: Within a range of a distance L extending from the particle surface along the radial direction of the particle to the particle interior, the mass concentration of Co gradually increases along the radial direction of the particle from the particle interior to the particle surface, where L=1 μm.
2. The positive electrode active material according to claim 1, characterized in that The L is 1.5 μm.
3. The positive electrode active material according to claim 1, characterized in that The Co mass concentration on the surface of the particle is 1.02 to 2 times, and optionally 1.1 to 1.8 times, the Co mass concentration at a distance L=1 μm extending from the particle radially to the inside of the particle.
4. The positive electrode active material according to any one of claims 1 to 3, characterized in that The mass concentration of Ni gradually decreases from the inside of the particle to the surface of the particle along the radial direction of the particle.
5. The positive electrode active material according to any one of claims 1 to 3, characterized in that The absolute value of the difference in mass concentration of Li and Mn at any two points in the particles is less than or equal to 20%.
6. The positive electrode active material according to any one of claims 1 to 5, characterized in that The positive electrode active material is represented by the following formula 1: Li x (Ni a Co b Mn c ) d M 1-d O 2-y A y Formula 1 Among them, 0.95≤x≤1.3, 0.3≤a≤0.7, 0.01≤b≤0.15, 0.1≤c≤0.5, a+b+c=1, 0.95≤d≤1, 0≤y≤0.1, M includes at least one selected from Zr, Sr, B, Ti, Mg, Sn, Tb, W, Nb and Al, and A includes at least one selected from S, N, F, Cl, Br and I.
7. The positive electrode active material according to any one of claims 1 to 6, characterized in that The volume distribution particle size Dv50 of the particles is in the range of 3.5 μm≤Dv50≤7.5 μm, optionally, 4 μm≤Dv50≤7 μm.
8. The positive electrode active material according to any one of claims 1 to 7, characterized in that The particles also have a coating layer. Optionally, the coating layer is an oxide or hydroxide of M', wherein M' includes at least one selected from Mg, Al, Ca, Ba, Ti, Zr, Zn, Nb, Sb, Ce, La, W and B.
9. The positive electrode active material according to claim 8, characterized in that The coating layer has a thickness of 0.001-0.5 μm, and optionally 0.01-0.1 μm.
10. A method for preparing a positive electrode active material according to any one of claims 1 to 9, characterized in that: The preparation method comprises: Mixing a lithium source, precursors of Ni, Co and Mn and optionally a compound containing a doping element M and a compound containing a doping element A, and performing a first sintering to obtain initial material particles; The starting material particles are mixed with a cobalt-containing compound and subjected to a second sintering to obtain particles containing lithium nickel cobalt manganese oxide.
11. The preparation method according to claim 10, characterized in that: The ratio of the mass of the cobalt-containing compound in terms of cobalt element to the mass of the particles containing lithium nickel cobalt manganese oxide is in the range of 2000-10000 ppm, and optionally, in the range of 4000-7000 ppm.
12. The preparation method according to claim 10 or 11, characterized in that: The molar ratio of Ni:Co:Mn in the precursor is in the range of (50-70):(6-25):(29-40), optionally, in the range of (55-65):(6-12):(29-33).
13. The preparation method according to any one of claims 10 to 12, characterized in that: The first sintering is carried out at 600° C.-1000° C. for 5 h to 25 h, and optionally at 650° C.-950° C. for 8 h to 20 h.
14. The preparation method according to any one of claims 10 to 13, characterized in that: The second sintering is performed in an oxygen-rich atmosphere. Optionally, the oxygen-rich atmosphere has a volume ratio of air to oxygen of between (0:10) and (8:2).
15. The preparation method according to any one of claims 10 to 14, characterized in that: The second sintering is carried out at 650° C.-800° C. for 5 h-7 h.
16. The preparation method according to any one of claims 10 to 15, characterized in that: The preparation method further comprises: The particles containing lithium nickel cobalt manganese oxide are mixed with an M' source and subjected to a third sintering to form a coating layer on the surface of the particles; optionally, the M' includes at least one selected from Mg, Al, Ca, Ba, Ti, Zr, Zn, Nb, Sb, Ce, La, W and B.
17. A secondary battery, comprising a positive electrode plate, characterized in that: The positive electrode plate comprises at least the positive electrode active material according to any one of claims 1 to 9, or the positive electrode plate comprises at least the positive electrode active material prepared by the preparation method according to any one of claims 10 to 16.
18. An electrical device, characterized in that: Includes the secondary battery as claimed in claim 17.
Citation Information
Patent Citations
Gradient type monocrystal-like positive electrode material and preparation method thereof
CN109962233A
Concentration gradient monocrystal positive electrode material and preparation method thereof
CN109962234A
Gradient single-crystal positive electrode material, preparation method and application
CN113782736A
Positive electrode active material, method for preparing same, and lithium secondary battery having positive electrode comprising same
CN114930574A
Lithium secondary battery
JP2000195517A
Cited By
Positive electrode active material and preparation method therefor, secondary battery, and electric device
EP4773240A1
Positive electrode active material and preparation method therefor, secondary battery, and electric device
WO2025092251A1